Utilitas zakat produktif terhadap penurunan kemiskinan di Provinsi Kepulauan Bangka Belitung - Rahmani, Zikri; Putra, Agung Rizki (AL-Muqayyad, 2024)
Zakat funds have a crucial role in alleviating poverty. Zakat funds not only provide direct assistance, but also empower through skills training programs and small businesses. Optimization and transparency of zakat fund management have the potential to reduce poverty in Bangka Belitung Province. The research method used in this research is Qualitative. The data collection technique used by researchers is a field survey with interviews and filling out questionnaires to poor people who are respondents and the Bangka Belitung Province Baznas as respondents and institutions that manage zakat funds, then to add to the analysis, literature and documentation studies are conducted. The results of this study indicate that the zakat distribution program carried out by Baznas of Bangka Islands Province is very much in accordance with the characteristics of poverty in the province.